Harold y el lapiz color morado - Johnson, Crockett, 1906-1975; Mlawer, Teresa ([New York] : Harper Arco Iris, 1995)
Harold provides himself with many adventures with his purple crayon.
Accelerated Reader
Keywords: Fantasy fiction -- Juvenile literature; Novela fantástica -- Literatura juvenil